Peculiarities of carcinomatous pleurisies in breast cancer (cytological diagnostic method) - O. G. Grigoruk; L. M. Bazulina; L. N. Dobrovolskaya; T. A. Maksimenko; M. N. Chechulin; A. F. Lazarev (ABV-press, 2014)
The specific features of carcinomatous pleurisies were studied in 119 patients with breast cancer (BC). The most characteristic properties of the structure of cells and the composition of pleural fluid were noted in infiltrating ductal and lobular BC. A differential diagnosis was made between mesothelioma (17%) and ovarian cancer (25%); it was difficult to perform it in lobular cancer.